Microalgae and low carbon energy production: a sustainable alternative to fossil fuels - Honório, Glaucio; Torres Netto, Alena; Costa Fernandes, Natalia; da Silva Amaral, Guilherme; Cordeiro Paredes Chagas, Leonardo; Pires Sant'Ana, Rebeca; Prado de Carvalho Vidal Parente, Pedro Henrique; Martins da Rocha Silva, Marcos Gabriel (Latin American Journal of Energy Research, 2024)
Due to the high global energy demand and environmental problems resulting from the burning of fossil fuels, today's society is embarking on a search for new, more sustainable energy sources, among which biomass stands out, with special attention being paid to microalgae. In addition to providing essential metabolites for the production of biofuels, microalgae can be grown in photovoltaic panels, obtaining solar energy through photosynthesis. Despite the substantial number of studies, obtaining biofuels from microalgae still faces some limitations. This study seeks to evaluate the technical and economic viability of using microalgae as a raw material for obtaining energy, in addition to presenting alternatives to overcome the limitations of the process.
Keywords: Biofuels; Bioenergy; Microalgae; Sustainable energy; Low carbon energy